Computación de alto desempeño : entorno de ejecución paralela basado en procesadores de arquitectura ARM (2015)
The following research describes the design and demonstrate the implementation of a parallel execution environment using eight slave nodes with ARM architecture processors that are assembled in Raspberry Pi SoC computers, for later add to the HPCLab cluster of the Tecnologica de Bol´ıvar University through the use of free and open source software and the job manager HTCondor. To this environment benchmark tests are done with the tool HPL (High Performance Linpack) and performance tests through the jobs sending with HTCondor. In this thesis explain the components and its functions too, it shows how install and configure the hardware and software used for the right and optimal performance of the system so that serves as a guide for the reader.